2020
DOI: 10.1101/2020.03.31.018283
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risperidone-induced changes in DNA methylation from peripheral blood in first-episode schizophrenia parallel neuroimaging and cognitive phenotype

Abstract: Today, second generation anti-psychotics such as clozapine and risperidone are the favored treatment for schizophrenia. Yet, the absence of relevant biomarkers that can decode their neurobiological effect shackles our ability to accurately predict and track response to treatment. While researchers have investigated DNA methylation as a biomarker for schizophrenia risk, none have performed a systematic analysis of the effect of antipsychotics upon DNA methylation. We hypothesize that disease-related methylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Similarly, another study showed that mNeurl1-deficient mice manifested behavioral abnormalities such as ethanol hypersensitivity and olfactory discrimination [78]. Moreover, genome-wide association studies (GWAS) also presented the involvement of Neurl1B along with other genes in the development of various neuropsychiatric disorders [77,79,80], thus, suggesting that Znf domain dysfunction by these miRNAs may cause wide transcription changes that contribute to the neuropsychology of MDD.…”
Section: Profile Of Dysregulated Cimirna Targets In Mddmentioning
confidence: 93%
“…Similarly, another study showed that mNeurl1-deficient mice manifested behavioral abnormalities such as ethanol hypersensitivity and olfactory discrimination [78]. Moreover, genome-wide association studies (GWAS) also presented the involvement of Neurl1B along with other genes in the development of various neuropsychiatric disorders [77,79,80], thus, suggesting that Znf domain dysfunction by these miRNAs may cause wide transcription changes that contribute to the neuropsychology of MDD.…”
Section: Profile Of Dysregulated Cimirna Targets In Mddmentioning
confidence: 93%
“…Briefly, the whole-genome methylation status was then examined in the above 76 samples by using the Illumina 450K GeneChip. This dataset has been previously used by our group ( Hu et al, 2020 ). We used the averaged value of all CpG sites in a gene to represent the DNAm level of this gene.…”
Section: Methodsmentioning
confidence: 99%
“…Whole genome methylation status was then examined in the above 76 samples ( Figure 1C ). This dataset has been previously used by our group ( 32 ).…”
Section: Methodsmentioning
confidence: 99%